Analisis Kebutuhan Model Pembelajaran Discovery Learning (Dl) pada Hasil Belajar Siswa Kelas VIII SMP Negeri 5 Lubuklinggau - Tarisa Juwa Mey Pranata; Wahyu Arini (Journal on Education, 2024)
The purpose of carrying out this needs analysis is to help teachers or educators make it easier to present the learning process and make it easier for students to understand the material being studied. This research refers to a qualitative research approach. The type of research carried out is descriptive. The subject of this research is the physics subject teacher at SMP Negeri 5 Lubuklinggau. After conducting a needs analysis, it was concluded that teaching materials were needed that could make it easy for students to understand the material being studied. It was concluded that teaching materials were needed that could make it easier for students to understand the material being studied. The solution for these teaching materials is teaching materials based on the discovery learning model.